Relationship between self-assessed and tested non-English-language proficiency among primary care providers - Diamond, Lisa; Chung, Sukyung; Ferguson, Warren; Gonzalez, Javier; Jacobs, Elizabeth A; Gany, Francesca (Medical care, 2014)
Individuals with limited English proficiency experience poor patient-clinician communication. Most studies of language concordance have not measured clinician non-English-language proficiency. To evaluate the accuracy of the self-assessment of non-English-language proficiency by clinicians compared with an oral proficiency interview. Primary care providers (PCPs) in California and Massachusetts. PCPs first completed a self-assessment of non-English-language proficiency using a version of the Interagency Language Roundtable (ILR) Scale, followed by the Clinician Cultural and Linguistic Assessment (CCLA), a validated oral proficiency interview. We used nonparametric approaches to analyze CCLA scores at each ILR scale level and the correlation between CCLA and ILR scale scores. Sixteen PCPs in California and 51 in Massachusetts participated (n=67). Participants spoke Spanish (79%), followed by Cantonese, Mandarin, French, Portuguese, and Vietnamese. The respondents self-assessed as having "excellent" proficiency 9% of the time, "very good" proficiency 24% of the time, "good" proficiency 46% of the time, "fair" proficiency 18% of the time, and "poor" proficiency 3% of the time. The average CCLA score was 76/100. There was a positive correlation between self-reported ILR scale and CCLA score (σ=0.49, P<0.001). The variance in CCLA scores was wider in the middle categories than in the low or high ILR categories (P=0.003). Self-assessment of non-English-language proficiency using the ILR correlates to tested language proficiency, particularly on the low and high ends of the scale. Participants who self-assess in the middle of the scale may require additional testing. Further research needs to be conducted to identify the characteristics of PCP whose self-assessments are inaccurate and, thus, require proficiency testing.